2019
DOI: 10.1097/cce.0000000000000006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Peer Support Model Using Experience-Based Co-Design to Improve Critical Care Recovery

Abstract: Objectives: To use experience-based co-design to identify the key design requirements of a peer support model for critical care survivors; understand the use of the experience-based co-design method from clinician, patients, and family perspectives. Design: Using experience-based co-design, qualitative data about participants’ preferences for a peer support model were generated via workshops. Participants’ perspectives of experience-based co-design were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Maher et al 16 experience of a participatory health service design process and found that the methods applied during the process, such as story-sharing and emotional mapping, were effective in establishing working relationships among the participants involved. More recently, Haines et al 18 evaluated participants' experience of co-designing a peer support model and found that patients and families appreciated feeling valued and heard and that clinicians found the approach beneficial.…”
Section: Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Maher et al 16 experience of a participatory health service design process and found that the methods applied during the process, such as story-sharing and emotional mapping, were effective in establishing working relationships among the participants involved. More recently, Haines et al 18 evaluated participants' experience of co-designing a peer support model and found that patients and families appreciated feeling valued and heard and that clinicians found the approach beneficial.…”
Section: Bymentioning
confidence: 99%
“…Bowen et al evaluated participants’ experience of a participatory health service design process and found that the methods applied during the process, such as story‐sharing and emotional mapping, were effective in establishing working relationships among the participants involved. More recently, Haines et al evaluated participants’ experience of co‐designing a peer support model and found that patients and families appreciated feeling valued and heard and that clinicians found the approach beneficial. Previous studies of co‐design experiences have applied the NHS experience‐based co‐design (EBCD) framework, a structured, stepwise approach that uses storytelling to gather patient and staff experiences to identify opportunities for improvements and inform co‐design groups working on the identified areas…”
Section: Introductionmentioning
confidence: 99%
“…(2) developing and disseminating educational materials to clinicians working in postacute care facilities and the outpatient setting, such as this recent perspective on sepsis survivorship geared towards physical therapists 53 ; and (3) incorporating education on sepsis sequelae into medical school curriculum, professional society conferences, and continuing medical education opportunities. 67 ; and (4) co-design of critical illness follow-up clinics by patients and clinicians 68,69 .…”
Section: Shorter-term Priority 2: Developing and Disseminating Educatmentioning
confidence: 99%
“…Second, there is growing interest in the critical care community to improve ICU survivorship and address post-ICU impairments. Despite the lack of supporting evidence ( 24 , 26 ), one key intervention has been the establishment of post-ICU recovery programs globally ( 27 , 28 , 34 ). This review, along with the international consensus conference recommendations ( 32 ), can be used to inform the identification of patients who are more likely to encounter new problems or worsening of pre-existing problems following ICU discharge who may benefit from structured recovery programs.…”
Section: Discussionmentioning
confidence: 99%